Redox modifications in synaptic components as biomarkers of cognitive status, in brain aging and disease - Munoz, Pablo; Ardiles, Alvaro O.; Perez-Espinosa, Boris; Nuñez Espinosa, Cristian Andrés; Paula-Lima, Andrea; Gonzalez-Billault, Christian; Espinosa Parrilla, Maria Yolanda (My University, 2020)
Aging is a natural process that includes several changes that gradually make organisms degenerate and die. Harman's theory proposes that aging is a consequence of the progressive accumulation of oxidative modifications mediated by reactive oxygen/nitrogen species, which plays an essential role in the development and progression of many neurodegenerative diseases. This review will focus on how abnormal redox modifications induced by age impair the functionality of neuronal redox-sensitive proteins involved in axonal elongation and guidance, synaptic plasticity, and intercellular communication. We will discuss post-transcriptional regulation of gene expression by microRNAs as a mechanism that controls the neuronal redox state. Finally, we will discuss how some brain-permeant antioxidants from the diet have a beneficial effect on cognition. Taken together, the evidence revised here indicates that oxidative-driven modifications of specific proteins and changes in microRNA expression may be useful biomarkers for aging and neurodegenerative diseases. Also, some specific antioxidant therapies have undoubtedly beneficial neuroprotective effects when administered in the correct doses, in the ideal formulation combination, and during the appropriate therapeutic window. The use of some antioxidants is, therefore, still poorly explored for the treatment of neurodegenerative diseases such as Alzheimer's disease.
Keywords: brain aging; oxidative stress; redox modifications; micrornas; alzheimer's disease